Intraspecific and sex-dependent variation of leaf traits along altitude gradient in the endangered dioecious tree Taxus fuana Nan Li & R.R. Mill - Li, Tian-Xiang; Shen-Tu, Xiao-Lu; Xu, Li; Zhang, Wei-Jun; Duan, Jun-Peng; Song, Yao-Bin; Dong, Ming (Frontiers in Plant Science, 2022)
Plant intraspecific trait variation (ITV) including sex-dependent differences are matters of many ecological consequences, from individual to ecosystem, especially in endangered and rare species. Taxus fuana is an endanger dioecious species with small and isolated populations endemic to Himalayas regions. Little is known about its trait variation between sexes, and among populations. In this study, 18 leaf traits from 179 reproductive trees (males and females) along the altitude (2600-3200m a.s.l.) of the T. fuana populations distributed in the Gyirong County, Tibet, China, were measured. ITV and sources of variation in leaf traits were assessed. Relationship between leaf traits of males and females and altitude was analyzed separately. Variation in leaf traits of T. fuana ranged from 3.1% to 24.2%, with the smallest in leaf carbon content and the largest in leaf thickness to area ratio. On average 78.13% of the variation in leaf traits was from within populations and 21.87% among populations. The trends in leaf width, leaf nitrogen to phosphorus ratio, leaf carbon to nitrogen ratio, leaf carbon isotope ratio, and leaf nitrogen isotope ratio in relation to altitude were the same for males and females. Leaf length to width ratio varied significantly with altitude only in males, while leaf phosphorus content, leaf nitrogen content and leaf carbon to phosphorus ratio varied significantly with altitude only in females. The correlation coefficients of most leaf traits of females with altitude were larger than that of males. In the relationship between leaf traits, there was a high similarity among males and females, but altitude was accounted for more explanation in females than in males. Our results suggested that the variation in leaf traits of T. fuana was small and did not dominate the interspecific competition in the local communities. Adaptation to altitude gradient of T. fuana might through altering nutrient storage processes and water use efficiency. Adaptation of male and female T. fuana to environmental changes showed differences, where the males were more tolerant and the females responded much to altitude. The differences in adaptation strategies between male and female T. fuana may be detrimental to the maintenance of their populations.